A atuação da Associação Mato-Grossense de Pesquisa e Apoio à Adoção nas práticas adotivas em Cuiabá-MT - Gola, Jéssica de Souza (2022)
This research starts from the observations of events and activities of Ampara, an Adoption Support Group that operates in the state of Mato Grosso, to analyze its operation in the administrative, political and legal spheres. The observed events and actvities happend betwen the Years 2019 and 2021 and the analyzes were realized of participant observation, interviews and recordings of online events. The goal of this research is to analyze the definitions of kinship and family that guide and lead the Ampara actions, as well as others groups associated with Angaad (Nacional Association of Adoption Support Groups) that participated in the analyzed events, in the administrative, political and legal sphere.